THE EFFECT OF GIANT SNAKEHEAD(Channa micropeltes)EXTRACT ON THE NUMBER OF MACROPHAGE IN DIABETES MELITUS WOUND HEALING (Research report) - Khairunnida Khairunnida; Amy Nindia Carabelly; Maharani Lailyza Apriasari (Dentino : Jurnal Kedokteran Gigi, 2019)
Background:Giant snakehead contains albumin and omega-6 fatty acids which play an important role in diabetes mellitus wound healing. Wounds in people with diabetes mellitus have low level of albumin, thus inhibiting the macrophage function. Objective: To prove the effect of giant snakehead extract of 16mL/Kg dose of rats’ weight toward the number of macrophage on wistar rats’ back wounds with diabetes mellitus in day 4, 8 and 14. Method and Materials: This study applied pure experimental method with posttest-only control design. This study 36 wistar rats as sample which divided into 9 groups; group of giant snakehead extract with 16mL/Kg dose of rats’ weight, positive control group using haruan fish extract with 13.54mL/Kg dose of rats’ weight, and negative control group using BR2 feed. Results: The test result of One-way ANOVAon day 4 (p=0.022), day 8 (p=0.251) and day 14 (0.028). The test result of Post-hoc LSD showedthat there wereno significant differences on day 4 and 14 (p>00.5) between the groups of the giant snakehead extract and haruan fish extract. There wassignificant difference (p<00.5) between groups of the giant snakehead extract and BR2 feed. Conclusion: It can be concluded that giant snakehead extract at 16 mL / kg dose administered orally may increase the number of macrophage in wistar rat (Rattusnovergicus) induced diabetes mellitus back woundon day 4 and decreased macrophage cell count onday 8 and day 14.